VISTA in hematological malignancies: a review of the literature - Yuanjia Duan; Yuanjia Duan; Yuanjia Duan; Xiaotong Ren; Xiaotong Ren; Xiaotong Ren; Xinyu Guo; Xinyu Guo; Xinyu Guo; Jiayi Xie; Jiayi Xie; Jiayi Xie; et al. (Frontiers in Immunology)
In recent years, tumor immunotherapy has become an active research area, with the emergence of immune checkpoint inhibitors (ICIs) revolutionizing immunotherapy. Clinical evidence indicates that programmed cell death protein 1 (PD-1) monoclonal antibodies and other drugs have remarkable therapeutic effects. V-domain Ig suppressor of T-cell activation (VISTA) is a new type of immune checkpoint receptor that is highly expressed in various tumors. It is co-expressed with PD-1, T-cell immunoglobulin domain, mucin domain-3 (Tim-3), T-cell immunoglobulin, and immunoreceptor tyrosine-based inhibitory motif domain (TIGIT) and is associated with prognosis, which suggests that it may be a target for immunotherapy. As an immune checkpoint receptor with no mature drugs, VISTA is highly expressed in acute myeloid leukemia (AML), multiple myeloma (MM), and other hematological malignancies; however, its pathogenic mechanism should be defined to better guide treatment.